Extra-articular distal tibia fibula fracture managed with single posterolateral approach: a case report - Mahajan, Neetin P.; G. S., Prasanna Kumar; Patil, Tushar C.; Pande, Kartik P.; Pawar, Harish (International Journal of Research in Orthopaedics, 2021)
Extra-articular distal tibia fractures involve distal tibia approximately 4 cm within tibia plafond with no articular extension. The proper preoperative care, planning and selection of surgical approach is very essential to prevent postoperative wound-related complications. We present a case of a 29 year female patient, presented with left ankle pain and swelling with a wound over the medial aspect of the ankle. X-ray of the left ankle showed extra-articular distal tibia fibula fracture with no neurovascular deficit. We managed both the fractures with open reduction and internal fixation using a single posterolateral approach. At present 1 year follow-up, the patient is having a good range of ankle motion with radiological union with no implant failure and wound-related complications. Extra-articular distal tibia fibula fracture fixation using single posterolateral approach is a viable alternative approach to medial or anterolateral approach in cases of medial or anterior soft tissue problems. It helps in getting a better functional outcome, early mobilisation with less wound-related complications.